Simulation of Ultra-Short Laser Pulses Propagation and Ionization in Dual-Gas-Cells to Enhance the Quasi-Phase Matching of Harmonics Generation in Plasmas - Wameedh Adress (Directorate for Research and Community Services (LPPM) ITB, 2024)
A numerical model was designed and implemented to investigate the influence of plasma defocusing on laser characteristics. The effects of plasma defocusing were investigated by studying beam divergence, intensity reduction, and blue shifting. The diffusion of the ultra-intense laser beam in gas cells was within a Rayleigh range. Moreover, using dual-gas-cells, the impact of quasi-phase matching (QPM) on the creation of harmonic pulses in argon and hydrogen plasmas was studied. The alternating structure of argon and hydrogen gas cells showed a perfect build-up of the generated ultra-short harmonics pulses. The impact of electron density on laser diffusion and the creation of harmonic pulses were also investigated in this work. In the simulation, argon plasma with different plasma densities was used in an alternating structure to create dual-gas-cells and quasi-phase-matching. Noticeable conversion of the fundamental laser pulses to harmonics pulses was accomplished in the model by using the QPM concept.